Spinal neurofibromatosis with NF1 mutation in a classic neurofibromatosis type 1 family: A case report and literature review. Issue 1 (11th November 2019) - Ning, Zeqian; Yang, Zhiqian; Chen, Gaofei; Wu, Wenjiao; He, Longshuang; Sun, Yesheng; Cai, Dongpeng; Zhang, Wei
Abstract: Background: Spinal neurofibromatosis (SNF) is a related form of Neurofibromatosis type 1 (NF1) with a low incidence. Here, we report a SNF patient with NF1 (OMIM *613113) mutation in a classic NF1 family to enrich the case data. Methods: We presented the clinical data of a 27‐year‐old female suffered from SNF. Two NF1 individuals (the mother and the brother) in the patient's family were also described. In the SNF patient, tumors in cervical were removed by surgical operation after the spinal MRI evaluation. Hematoxylin‐eosin staining and immunohistochemistry were performed to better characterize the excised tumors. NF1 exons of the patient and her NF1 families were further sequenced by the next‐generation sequencing technology. Results: The patient developed irregular café‐au‐lait macules, multi‐subcutaneous nodules, recurrent numbness, and weakness of both lower extremities. Multiple neurofibromas were found in the whole spine by spinal MRI. Tumor‐like cells and hyperplasia of ganglion cells were found in the excised tissue by H&E staining and immunohistochemistry, respectively. One‐year follow‐up on the SNF patient showed that after the surgery lower limb pain, numbness and convulsion were completely relieved. A common germ‐line pathogenic mutation (NM_000267.3:c.1721 + 3A>G) was found in both the SNF patient and her classic NF1 families. Conclusion: A case of SNF with classic NF1 mutation in a classic NF1 family was identified for the first time, indicating that SNF may share the same gene mutation with NF1, while the different manifestation of NF1 and SNF may be related to gene modification. Abstract : A case of spinal neurofibromatosis with classic NF1 mutation (c.1721 + 3A>G) in a classic NF1 family was identified for the first time.